OFFENCES INVOLVING AN ELEMENT OF DISHONESTY: SECTION 27(a)(ii) OF THE ESTATE AGENCY AFFAIRS ACT 112 OF 1976 - Henk Delport (Obiter, 2022)
Section 27(a)(ii) of the Estate Agency Affairs Act 112 of 1976 disqualifies a person from being issued with a fidelity fund certificate if such person has at any time “been convicted of an offence involving an element of dishonesty”. The Afrikaans text (which was signed by the State President) is worded differently, and refers to “’n misdryf waarvan oneerlikheid ’n element is” (“an offence of which dishonesty is an element”). The current Constitution, unlike its predecessors, contains no provision stating expressly that in the event of a conflict between two versions of an Act the text signed by the President is to be given effect. It is submitted, however, that thereis no conflict between the two versions of section 27(a)(ii). Having regard to the ordinary rules relating to interpretation of statutes, the conclusion is reached that the section must be interpreted to mean that a person is disqualified from being issued with a fidelity fund certificate only if such person has been convicted of an offence of which dishonesty is an element. The article analyses court cases where the word “dishonesty” was discussed with reference to both common law and statutory offences. Reference is also made to the word “dishonesty” in a criminal law context. It is pointed out that for the purposes of section 27(a)(ii) dishonesty need not be a requirement of the offence, but must be an ingredient thereof. What must be looked at is the nature of the offence, not the context in which it was committed. The key question is: Can it be said, by applying the standards of reasonable and honest persons, that the nature of the offence, having regard to its description, is such that any person committing the offence would by necessary implication be acting dishonestly? If dishonesty is by necessary inference an ingredient of the offence it is immaterial for the purposes of section 27(a)(ii) that the person convicted of the offence had no intention to deceive. All offences are inherently wrongful, but dishonesty is not necessarily an element of all offences. Cheating or deceiving are key aspects of dishonesty. Offences which are morally repugnant are not dishonest per se. From a moral perspective it is arguable that there are degrees of dishonesty, but this is irrelevant for the purposes of section 27(a)(ii).